Comparative Transcriptome Analysis Reveals the Adaptation Mechanism to High Salinity in Litopenaeus vannamei - Luo, Zheng; Yu, Yang; Zhang, Qian; Bao, Zhenning; Xiang, Jianhai; Li, Fuhua (Frontiers in Marine Science, 2022)
As an euryhaline commercial species, the Pacific white shrimp Litopenaeus vannamei can be cultured under a wide range of salinities. However, different families showed various tolerance to high salinity. In order to elucidate the underlying mechanisms, a comparative transcriptome approach was used to find the differences between tolerant families and susceptible families at the transcriptional level. There were 98 and 58 differentially expressed genes (DEGs) between tolerant and susceptible families under normal and high salinity conditions, respectively. The DEGs up-regulated in tolerant families were mostly enriched in the biological process of response to stimulus. Nine crustacyanins (CRCN) encoding genes in this Gene Ontology (GO) term showed significantly higher expression level in the tolerant families than those in susceptible families, suggesting that crustacyanins might play important roles in shrimp tolerance to high salinity. After high salinity treatment, a total of 233 and 109 DEGs were identified from tolerant and susceptible families, respectively. Serine-type endopeptidase activity, serine-type peptidase activity and serine hydrolase activity were the top three GO terms in the tolerant families after high salinity treatment. Further analysis illustrated these three GO terms were also the top three enriched GO terms for the DEGs specifically up-regulated in the tolerant families after high salinity stress. Meanwhile, four genes annotated in serine proteases families in these three GO terms were up-regulated in the tolerant families but not changed in the susceptible families after high salinity stress. These results indicated that serine proteases should play key roles in shrimp tolerance to high salinity. This study provides important information for understanding the mechanism of shrimp tolerance to high salinity stress, and would be useful for further molecular breeding of shrimp varieties with high salinity tolerance.